Reading for Storyness Preclosure Theory, Empirical Poetics, and Culture in the Short Story - Lohafer, Susan (Johns Hopkins University Press, 2003)
The short story has been a staple of American literature since the nineteenth century, taught in virtually every high school and consistently popular among adult readers. But what makes a short story unique? In Reading for Storyness, Susan Lohafer, former president of the Society for the Study of the Short Story, argues that there is much more than length separating short stories from novels and other works of fiction. With its close readings of stories by Kate Chopin, Julio Cortázar, Katherine Mansfield, and others, this book challenges assumptions about the short story and effectively redefines the genre in a fresh and original way.In her analysis, Lohafer combines traditional literary theory with a more unconventional mode of research, monitoring the reactions of readers as they progress through a story-to establish a new poetics of the genre. Singling out the phenomenon of "imminent closure" as the genre's defining trait, she then proceeds to identify "preclosure points," or places where a given story could end, in order to access hidden layers of the reading experience. She expertly harnesses this theory of preclosure to explore interactions between pedagogy and theory, formalism and cultural studies, fiction and nonfiction. Returning to the roots of storyness, Lohafer illuminates the intricacies of classic short stories and experimental forms of surreal, postmodern, and minimalist fiction. She also discusses the impact of social constructions, such as gender, on the identification of preclosure points by individual readers. Reading for Storyness combines cognitive science with literary theory to present a compelling argument for the uniqueness of the short story.